FROM CONTENT TO CONTEXT: THE DEVELOPMENT OF THE FOOTYFIRST PROGRAM TO PREVENT LOWER LIMB INJURIES IN COMMUNITY AUSTRALIAN FOOTBALL. Issue 7 (11th March 2014) - Donaldson, A; Lloyd, D; Young, W; Barbery, G; Cook, J; Gabbe, B; Finch, CF
Abstract : Background: Developing injury prevention programs for community sport is challenging. The injury issues and interventions must be grounded in science and be both meaningful to, and implementable by, those involved in community sport. Objective: This presentation will detail the multi-stage iterative process used to develop FootyFirst, a community-Australian Football (AF) specific lower limb injury prevention program. Design: The scientific literature, clinical experience, expert and end-user consultations, community trials, theory-informed discussion, and graphic design and editorial expertise, were combined to develop FootyFirst. Setting: Community-AF. Results: Lower limb injuries were identified as the major injury concern and it was established that a combination of balance and control, eccentric hamstring, plyometric and strength exercises could be efficacious in preventing such injuries. The multi-disciplinary research team used evidence from the scientific literature, clinical experience and knowledge of the community-AF context in an iterative process to create and trial the exercises and progressions that were included in the first draft of FootyFirst. This draft was further refined through a Delphi process in which AF-specific lower limb injury prevention experts agreed on the appropriateness of including the proposed exercises in FootyFirst. Potential end-user groups (community-AF players, coaches, fitness coaches, sports trainers and administrators) provided feedback about the fit between FootyFirst and the implementation context including potential barriers and facilitators to widespread program adoption and implementation. Trials of FootyFirst were conducted to ensure it could be understood and delivered by community-AF coaches and completed by players. The research team then reviewed the entire program during discussions focused around the Diffusion of Innovations principles of relative advantage, compatibility, complexity, trialability and observability before expert graphic designers and editors were engaged to develop FootyFirst resources. Conclusions: The content-to-context process detailed in this presentation was successfully used to develop FootyFirst, an evidence-informed, expert-endorsed, context-specific community-AF lower limb injury prevention program.